2000
DOI: 10.1016/s0029-7844(00)00929-7
|View full text |Cite
|
Sign up to set email alerts
|

Noninflammatory ovarian masses in girls and young women

Abstract: The most frequent cause of an ovarian mass requiring surgery in a girl or young woman under 21 years of age is an ovarian cyst, which justifies consideration of a laparoscopic approach. Patient age rather than time of surgery predicted operative approach and surgeon type. Caution should be exercised in patients over age 12 months with a complex mass on ultrasound and clinical evidence of hormonal activity, as these masses are usually malignant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
54
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 15 publications
4
54
0
3
Order By: Relevance
“…When the clinical suspicion for ovarian malignancy remains low, most authorities recommend ovary-conserving surgery (2)(3)(4)(5). Our data demonstrate that the affected ovary resumes a normal size and volume postoperatively, suggesting that the attenuated ovarian cortex naturally resorbs.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…When the clinical suspicion for ovarian malignancy remains low, most authorities recommend ovary-conserving surgery (2)(3)(4)(5). Our data demonstrate that the affected ovary resumes a normal size and volume postoperatively, suggesting that the attenuated ovarian cortex naturally resorbs.…”
Section: Discussionmentioning
confidence: 67%
“…Historically, an oophorectomy has been advocated out of a fear of malignancy. Recent studies, however, report that the incidence of malignancy among adolescents undergoing surgical management of persistent ovarian neoplasms ranges between 4% and 9% (2)(3)(4)(5)(6). In accordance with the Children's Oncology Group, standard surgical staging should be performed when concern for malignancy is high (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even within the adolescent age group, the pathology varies depending on the patient's age. In a series of 140 patients, it was found that ovarian malignancy was more common in girls under 15, with ovarian cysts and benign tumours more likely in older patients [3]. This finding was confirmed in a larger series from the Mayo Clinic [4].…”
mentioning
confidence: 74%
“…Benign ovarian neoplasms rarely present in neonates, although they account for 30-40% of ovarian lesions in children and benign cysts account for 60% [2,3]. Benign follicular cysts develop from hormonal stimulation of the fetal ovary by maternal, placental, and fetal follicle stimulating hormones.…”
Section: Discussionmentioning
confidence: 99%